Indirect Evidence in Disclosing Cartel Violations Under Business Competition Law in Indonesia - Sari, Liani; Katjong, Revie Kurnia; Nurlia Mamonto, Andi Anisa; Ramli, Asmarani; Bakung, Dolot Alhasni (Jurnal Dinamika Hukum, 2024)
Cartels, or secret deals among competitors to set prices, limit production, or divide markets, pose a significant challenge to healthy competition and market integrity around the world, including in Indonesia. This study examines the use of indirect evidence, such as economic data and communication patterns, in uncovering such covert operations under the Indonesian Competition Law (Law No. 5 of 1999), using the normative juridical approach. The study uses statutory analysis to understand the legal framework, case analysis to explore the use of indirect evidence in law enforcement, and conceptual analysis to enhance theoretical understanding. This study analyzes the decisions of the KPPU and District Courts, KPPU regulations, and relevant legal frameworks to understand the applicability and challenges of using circumstantial evidence in legal proceedings. The results of the study make it clear that, despite its important role, the study identifies legal uncertainty and the need for corroborating evidence as the main obstacles to the effectiveness of indirect evidence. It reveals a significant gap in the acceptance and interpretation of indirect evidence between the KPPU and the judiciary, highlighting the need for clarity and consistency in the law. This review recommends the revision of Law No. 5 of 1999 and related procedural laws to include provisions for the acceptance and utilization of circumstantial evidence, improving the adjudication process of both the KPPU and the courts. This research contributes to Indonesia's understanding of competition law enforcement and promoting fair business practices.